Relationship between life aspirations, satisfaction of psychological needs, subjective vitality and happiness among undergraduate students of research universities in Malaysia - Ajri, Zahra (2017)
Traditionally, scholars and societies have focused on the negative side of human behaviour and ignored the positive side. Therefore, few studies have been conducted that look into happiness as the human life purpose. This has resulted in a knowledge gap regarding human well-being, especially in Malaysia. To address this gap, the present study has developed a new hypotheses that focuses on happiness and its’ related dynamics, rather than just concentrating on ill-being. Consequently, this study was designed to examine the relationship between life aspirations and happiness as well as the mediating role of psychological needs. To provide a valid foundation for predicting well-being among undergraduate students, the current study utilized goal contents theory (GCT), basic psychological needs theory (BPNT), and vitality concept to develop the theoretical framework. Specifically, the current research has examined an additional concept i.e. vitality, by employing a serial multiple mediator model. Moreover, it was examined whether extrinsic goals have the same function as intrinsic goals on happiness. In addition, this study was designed to examine the moderating role of autonomy on the relationship between intrinsic goals and happiness among undergraduate students in Malaysia. A cross-sectional study using multi-stage cluster random sampling method was conducted on 400 undergraduate students from three public universities (UM, UKM and UPM) in Klang Valley, Malaysia. A self-administered questionnaire package containing assessments of goal contents / aspiration index, basic psychological need satisfaction, subjective vitality and short depression-happiness scale was distributed among respondents. Data from the survey was then subjected to the partial least squares (PLS) path modeling approach to study the relationship between variables by using Smart-PLS. Results have supported the research hypotheses and indicated that life aspirations (intrinsic goals and extrinsic goals) of undergraduate students are positively and significantly related to their happiness. Moreover, the findings of this study have shown that psychological needs and vitality are partially mediating the relationship between intrinsic goals and happiness. Furthermore, the current study has applied a more comprehensive mediation model. Serial multiple-mediation path was modeled in the present study to advance the understanding of happiness among students. In this path, vitality is in fact the second mediator and comes after psychological needs. This path commences from intrinsic goals, being mediated by the path of psychological needs-vitality, and finally results in happiness. Moreover, findings indicated that extrinsic goals have no relationship with vitality and psychological needs. Findings have supported a model based on BPNT theory and GCT theory and suggested that psychological need fulfillment and subjective vitality would be key factors in increasing happiness among students. Findings also highlight the importance of autonomy as a moderator on the relationship between intrinsic goals and happiness. The implication of this study would apply to all parties including parents, teachers, university policy makers, media and health specialists. All parties involved attempting to increase well-being and happiness in university and society should encourage students to improve their relationships, personal growth, community affiliation, and spirituality as their intrinsic goals. This strategy will help students to satisfy their basic psychological needs and consequently lead to more energy and happiness in their life.